(untitled) - Eagleton, Terry; Terry Eagleton (Oxford,New York, 2005)
Holy Terror is a profound and timely investigation of the idea of terror, drawing upon political, philosophical, literary, and theological sources to trace a genealogy from the ancient world to the modern day. Rather than add to the mounting pile of political studies of terrorism, Terry Eagleton offers here a metaphysics of terror with a serious historical perspective. Writing with remarkable clarity and persuasive insight he examines a concept whose cultural impact predates 9/11 by millennia
Includes bibliographical references (p. [141]-144) and index
Keywords: Terrorism; Violence; Terror